PELATIHAN PENGEMBANGAN KONTEN DIGITAL MENGGUNAKAN ALAT DESAIN BERBASIS WEB DAN MOBILE - Arie Rachmad Syulistyo; Milyun Ni’ma Shoumi; Septian Enggar Sukmana; Cahya Rahmad; Ariadi Retno Tri Hayati Ririd; Anugrah Nur Rahmanto; Devi Zettyara (Jurnal Pengabdian kepada Masyarakat, 2024)
The internet and information systems are rapidly evolving, with technology becoming increasingly sophisticated worldwide. Consequently, entrepreneurs can now offer valuable information or conduct business from the convenience of their own homes. In this context, it is expected that PKK mothers, specifically those affiliated with the PKK group RW 07 in Purwodadi Village, Blimbing District, Malang City, should seize these opportunities by utilizing digital content. The PKM Community Service Team is encouraged to offer training in digital content creation in light of advancements in information technology. The team is currently seeking web-based and mobile design tools that can be readily utilised by PKK group mothers. The digital content produced can be employed to advertise activities within the RW community or their own merchandise. Following the implementation of community service, the PKM team evaluated the PKK group with 5 questions. The PKK group deems the presented material useful and the program beneficial for enhancing their skills. Overall, the PKK group expresses satisfaction with the program's implementation. Additionally, following observations made by the PKM Team, the information we offer has been utilized to produce captivating content for broadcasting announcements on social media platforms belonging to the PKK organization.